2D Nanosheets: Hydraulic Power Manufacturing for Highly Scalable and Stable 2D Nanosheet Dispersions and Their Film Electrode Application (Adv. Funct. Mater. 43/2018). (22nd October 2018) - Jeong, Jae‐Min; Kang, Heon Gyu; Kim, Hyung‐Jin; Hong, Seok Bok; Jeon, Hyeonyeol; Hwang, Sung Yeon; Seo, Donghyuk; Kwak, Byeong Eun; Han, Young‐Kyu; Choi, Bong Gill; Kim, Do Hyun
Abstract : In article number1802952, Young‐Kyu Han, Bong Gill Choi, Do Hyun Kim, and co‐workers report a fast, scalable, and versatile hydraulic power process to make highly stable 2D nanosheet dispersions. Highly stable 2D nanosheet dispersions can be conveniently processed by vacuum filtration and inkjet printing for highly conductive circuits and high‐performance energy storage film electrodes.